A derivative-free filter method for solving nonlinear complementarity problems - Nie, Pu-yan; Fan, Jin-yan (Applied mathematics and computation, 2005)
In this work, nonlinear complementarity problems (NCPs) are considered. Some NCPs, which come from practice, have no derivatives or it is very difficult to obtain their derivatives. Derivative-free methods are hence considered. Generalized pattern search (GPS) method, as a kind of derivative-free method, plays a very significant role. We combine generalized pattern search method with filter method to attack NCPs because one can analyze the theory of generalized pattern search filter method without sufficient reduction conditions and avoid using of derivatives. Some interesting results are obtained in this work without sufficient reduction conditions. Furthermore, generalized pattern search filter method is efficient to some special problems.